Impact of the Native SiO2 Surface Layer on the Electron Transfer at Amorphous Si Electrodes. (24th November 2015) - Bülter, Heinz; Sternad, Michael; Wilkening, Martin; Wittstock, Gunther
Abstract : The electron transfer at uncharged microstructured and planar amorphous (a-)Si was characterized using the feedback mode of scanning electrochemical microscopy (SECM) and 2, 5-di- tert -butyl-1, 4-dimethoxybenzene as redox mediator in carbonate electrolytes. Approach curves and images demonstrate that the electron transfer rate at pristine a-Si is relatively small due to the native SiO2 surface layer. In addition, the electron transfer rates show local variations because of the heterogeneous coverage of SiO2 . After removal of the SiO2 layer, the effect of the solid electrolyte interphase (SEI) on electron transport rate can be studied. The SiO2 layer is at least partially removed by approach curve contact and scratching with the microelectrode probe. After SiO2 removal, the electron transfer rates increase strongly and remain heterogeneous.